Pergeseran Interpretasi Kisah Pernikahan Nabi dengan Zaynab Binti Jahsy dalam Q.S. Al-Ahzab (33): 37: #Pergeseran Interpretasi #studi komparasi tafsir #tafsir tematik - Muqit, Abd. (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
Abstract Shift in exegesis of Al-Qur’an can be found in many issues, such as the Prophet’s marriage issue to Zaynab Binti Jahsy. Many views develop between muslim scholars and western scholars. This study will explain many variations exegesis of classical, medieval, and modern-contemporary scholars who elaborate on exegesis from classical era specially from Maqātil Bin Sulaimān and Yahyā Bin Sallām, medieval era from Al-Ṭabarī and Al-Wāhidī, and modern-contemporary era from Ibn ‘Āsyūr and Izzah Darwazah. Generally, the discussion in this study is about how Q.S. Al-Ahzāb (33): 37 talks the story of Prophet’s marriage to Zaynab Binti Jahsy from the mufassir’s perspective and specifically will discuss shifts in exegesis by answering two questions: a) how the shifts in exegesis of story of Prophet’s marriage to Zaynab Binti Jahsy and b) what are implications for the study of Qur’anic story. The questions have come to a conclusion that a shift in exegesis of Al-Ahzāb (33): 37 was real specially in sabab nuzūl, narration of the story, and exegesis from mufasir. Exegesis from classical era and medieval era has significant implications for the study of Qur’anic story in the mainstream view.